Pengaruh Marketing Mix 4P dan Perceived Quality Terhadap Purchase Decision Smartphone Vivo - Liandri Darma Putra; Eko Harry Susanto (Universitas Tarumanagara, 2019)
The purpose of this study is to analyze the effect of the marketing mix (product, price, promotion and place) and perceived quality on purchasing decisions. The research implemented quantitative method, in which questionnaire were distributed to a total of 120 respondents, thus enabling the data to be analyzed. Data were collected from respondents in Jakarta Barat regions. Data were analyzed by SPSS version 20.00 for windows using multiple linier regression method. After conducting data analysis, it was revealed that place and perceived quality have a significant impact on purchase decision. Meanwhile product, price and promotion doesn’t have a positive impact toward purchase decision. But all variables simultaneously have a significant effect toward purchase decision.